2022
DOI: 10.1111/desc.13226
|View full text |Cite
|
Sign up to set email alerts
|

What are the kids doing? Exploring young children's activities at home and relations with externally cued executive function and child temperament

Abstract: Research Highlights• Explored relation between children's activities at home and externally cued executive function in 93 3-to 5-year-old children at home at the beginning of the COVID-19 pandemic • More time and variety in less-structured activities was related to externally cued executive function, controlling for age, family income, caregiver education, and verbal knowledge • Caregivers were more involved in their children's less-structured versus structured activities • Caregiver ratings of children's temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 54 publications
1
10
0
1
Order By: Relevance
“…Sullivan et al (2022) observed that behavioral and ERP markers of inhibitory control were all associated with the IQ scores, and 5-yearolds children who experienced higher levels of psychosocial adversity had a lower accuracy of the task and lower IQ scores. Stucke et al (2022) examined home activities during the COVID-19 pandemic and time and variety of less-structured activities (wide range of activities permitting choice and interaction with caregiver) were related to successful switching on the Dimensional Change Card Sort at preschool age, controlling for age, family income, caregiver education, and verbal knowledge. Moreover, executive function performance can be substantially influenced by prior knowledge and immediate contextual factors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sullivan et al (2022) observed that behavioral and ERP markers of inhibitory control were all associated with the IQ scores, and 5-yearolds children who experienced higher levels of psychosocial adversity had a lower accuracy of the task and lower IQ scores. Stucke et al (2022) examined home activities during the COVID-19 pandemic and time and variety of less-structured activities (wide range of activities permitting choice and interaction with caregiver) were related to successful switching on the Dimensional Change Card Sort at preschool age, controlling for age, family income, caregiver education, and verbal knowledge. Moreover, executive function performance can be substantially influenced by prior knowledge and immediate contextual factors.…”
mentioning
confidence: 99%
“…Stucke et al. (2022) examined home activities during the COVID‐19 pandemic and time and variety of less‐structured activities (wide range of activities permitting choice and interaction with caregiver) were related to successful switching on the Dimensional Change Card Sort at preschool age, controlling for age, family income, caregiver education, and verbal knowledge. Moreover, executive function performance can be substantially influenced by prior knowledge and immediate contextual factors.…”
mentioning
confidence: 99%
“…According to Doebel (2020), success in the task may be predicted by factors such as prior knowledge and experiences. Indeed, Stucke, Stoet, and Doebel (2022) provide evidence that 3-to-5-year-olds' success in the DCCS is predicted by time doing less structured and more self-directed activities, such as play, as opposed to more structured and more adult-directed activities, such as classroom instruction. Alternatively, according to Perone et al (2021), success indicates that the child has learned the visual dimensional label (color or shape), as measured by neural responses (Buss & Kerr-German, 2019).…”
Section: Summary and Implicationsmentioning
confidence: 97%
“…We propose that goals are self-directedly identified through accumulated knowledge (Doebel, 2020) which guides how children keep track of the different sub-goals and goals, before their selection and execution. Indeed, as children gained knowledge from the contextual information in their environment such as in less-structured activities, this predicts better performance in self-directed control (Barker et al, 2014) and externally driven control (Stucke et al, 2022).…”
Section: Context-tracking and Goal Selectionmentioning
confidence: 99%